The History of the American Comic Book, Revised - Review of Comic Books Incorporated: How the Business of Comics Became the Business of Hollywood by Shawna Kidman, University of California Press, 2019 - Asher Guthertz (Global Storytelling)
This book review of Shawna Kidman’s Comic Books Incorporated: How the Business of Comics Became the Business of Hollywood highlights the works crucial intervention in comic book studies. In the face of a rote history of the comic book as a persistent subcultural phenomenon, Kidman argues that attending to the various legal, social, and industrial infrastructures of comic book culture can illustrate the ebbs and flows of comic book popularity, its shifts in genres and tone, and its movements across mediums as the path of a “fundamentally corporate” medium, “a dominant form in a culture built to support its growth.” The review sketches the book’s chapters, which each focus on a different form of infrastructure relevant to the history of the comic book: distribution, copyright law, subculture, and financing. I end with further areas of research suggested by this work, particularly within the field of historical ethnography. While Comic Books Incorporated tells its story through the history of industrial logics, a closer attention to comic book reading practices during the time in which this story takes place can deepen our understanding of the transformation from a mass medium with seemingly equal readership across gender to a niche subcultural fascination for college aged white men.Throughout the text, the work demystifies a prevailing narrative that the comics industry and fanbase tells: that the success of the medium is due to the inherent quality of the source material. This book thoroughly demonstrates that the evolution of the comic book was driven not by creativity and iconoclasm, but by corporate logic.